Investigation of photophysical, photochemical and aggregation properties of A3B type Zn(II) and In(III) phthalocyanines containing tert-butyl and benzodioxane groups - Penlik, Yunus; Avciata, Oguzhan; Gorduk, Semih (ELSEVIER, 2025)
In the present study, we described synthesis A3B type unsymmetrical zinc(II) and indium(III)chloro phthalocyanines containing tert-butyl and 2,3-dihydro-1,4-benzodioxin-2-ylmethoxy groups and examined their photo- physicochemical and aggregation properties. Firstly, the precursor phthalonitriles which are used to obtain phthalocyanine compounds bearing different metal ions were synthesized. In the next step, the synthesized [2,9,16-Tri-(4-tert-butylphenoxy)-23-(4-((2,3-dihydrobenzo[b][1,4]dioxin-2-yl)methoxy)-phthalocyaninato zinc (II) (ZnPc) and [2,9,16-Tri-(4-tert-butylphenoxy)-23-(4-((2,3-dihydrobenzo[b][1,4]dioxin-2-yl)methoxy)phthalocyaninato indium(III)CI (InPc) compounds were characterized by applying various spectroscopic techniques. The photochemical, photophysical, and aggregation behaviours of compounds were examined in DMSO and DMF solvents. In addition, synthesized compounds did not showed aggregation in these solvents. The calculated singlet oxygen quantum yield values in DMSO are 0.73 for ZnPc, and 0.78 for InPc in and these in DMF are 0.60 for ZnPc, and 0.69 for InPc after photochemical applications. Considering the collected data, it was observed that the addition of substituents increased the therapeutic efficacy. As a result, all synthesized Pc derivatives display desirable singlet oxygen, photodegradation, fluorescence and aggregation properties.
Keywords: Phthalocyanine; Asymmetric; Photophysicochemical; A3B type; Benzodioxane; TETRA-SUBSTITUTED ZINC(II); PHOTODYNAMIC THERAPY; CANCER; MECHANISMS; PDT; Chemistry